The Growth of Beauveria bassiana on Corn Waste Medium - Dyah Rini Indriyanti; Siti Harnina Bintari; Ning Setiati; Puput Roy Purnawati (International Conference on Science, Education, and Technology, 2022)
The purpose of this study was to analyze the density and viability of Beauveria bassiana grown on corn waste medium with 1% NPK (Nitrogen Phosphate Potassium) supplementation. This experimental study used a completely randomized design with 3 treatments and 9 repetitions. Each growth medium consisted of 25 grams of corn waste supplemented with NPK 1% with a dose of 0 mL (P0), 2mL (P1), and 3 mL (P2). The results of this study showed that the highest fungal density (16.72x108 conidia/mL) and viability (44.66%) were obtained from P2 treatment. It can be concluded that 1% NPK on corn waste medium affect the density and viability of Beauveria bassiana.